OPTIMALISASI PADI SAWAH DENGAN BIOAMELIORAN BOKASHI JERAMI PADI DAN BOKASHI ECENG GONDOK - Rusmana, Azhar Indra; Tasmin; Fitria, Syifa (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Indramayu Regency is one of the rice barns in Indonesia with high productivity, producing agricultural waste in the form of straw in large quantities. However, the suboptimal management of straw, such as its direct burning in fields, causes environmental pollution and the loss of soil nutrients. On the other hand, the growth of water hyacinth in Indramayu waters causes problems for the aquatic ecosystem. This study investigates how bokashi, made from rice straw and water hyacinth, functions as a bioameliorant to improve rice development and productivity. This study was conducted using a factorial approach in a Randomized Block Design (RBD) with two factors, namely the dose of rice straw bokashi (0, 10, and 20 tons ha-1) and the dose of water hyacinth bokashi (0, 10, and 20 tons ha-1). It is proven that the use of bokashi and water hyacinth as bioameliorants increases rice development and productivity. According to the research results, there was a significant interaction between the two types of bokashi on plant height at 14, 28, 42, and 56 HST, number of leaves at 42 and 56 HST, and weight of 1,000 grains as well as harvest yield. The optimal dose recommended to achieve the best results is 10 tons ha-1 of rice straw bokashi and 20 tons ha-1 of water hyacinth bokashi. The implementation of this technology has the potential to increase agricultural productivity sustainably and reduce negative impacts on the environment through more efficient utilization of agricultural waste and aquatic ecosystems.